Herbivory and presence of a dominant competitor interactively affect salt marsh plant diversity. (15th October 2017) - Daleo, Pedro; Alberti, Juan; Bruschetti, Carlos Martín; Martinetto, Paulina; Pascual, Jesús; Iribarne, Oscar
Abstract: Question: Do herbivory and the presence of a dominant grass competitor interactively affect herbaceous communities and assembly rules in a SW Atlantic salt marsh? Location: Upper salt marsh, Mar Chiquita coastal lagoon, Argentina. Methods: We performed a field factorial experiment over 4 yr to evaluate the separate and interactive effects of (1) herbivory and (2) competition with the dominant grass species (i.e. Spartina densiflora ) on the salt marsh subordinate plant community. The factorial design includes dominant grass removal and herbivory manipulation. Results: Our results show that herbivory and presence of the dominant competitor interactively affect subordinate plant cover and diversity. Results further indicate that, in the presence of the dominant competitor, patch‐to‐patch variation in subordinate species composition is lower than expected at random, a result consistent with the expected outcomes of deterministic exclusion following light competition. Removal of the dominant grass nevertheless led to patch‐to‐patch dissimilarity in subordinate species composition, far from the dissimilarity expected at random, indicating increased importance of deterministic processes that drive communities to diverge. Conclusion: Our results show that the conditional effect of herbivory on plant diversity can be determined by the presence of a single plant species. Dominant plant species, in addition, may not only affect plant species diversity by determining the number and identity of subordinate species in a given patch (i.e. α‐diversity) but also by affecting spatial variability through habitat homogenization. Abstract : We evaluated how herbivory and the presence of a dominant grass competitor affect salt marsh plant communities. Our results show that herbivory and competition can interact to set plant community composition; the presence of a dominant plant can change the direction of herbivory effect. Dominant plants, in addition, can decrease species diversity by competitive exclusion and by decreasing environmental heterogeneity.